Psychological Distress and Quality of Life in Families With a Germline CDKN2A Pathogenic Variant - A. M. Onnekink; D. C. F. Klatte; J. E. vanHooft; S. H. van denBerg; S. M. S. van derZwaan; R. vanDoorn; S. C. H. Hinnen; T. P. Potjer; E. M. A. Bleiker; M. E. vanLeerdam (Molecular Genetics & Genomic Medicine, 2025)
ABSTRACT Background Individuals with a germline CDKN2A pathogenic variant (PV) have an increased lifetime risk of melanoma and pancreatic cancer. It is unknown whether the CDKN2A PV impacts quality of life (QoL). Therefore we aimed to assess QoL and psychological distress in families affected by the PV. Methods This cross‐sectional study included confirmed carriers and those with a 50% likelihood of carrying the PV (at‐risk carriers) under cancer surveillance who were invited to complete a one‐time questionnaire. Both confirmed and at‐risk carriers are offered skin surveillance, whereas only confirmed carriers aged 40 years or older can participate in pancreatic surveillance. Results In total, 59/247 (24%) individuals under skin surveillance only (skin surveillance group) and 188/290 (65%) individuals under both skin and pancreatic cancer surveillance (pancreatic surveillance group) responded. In both surveillance groups, health‐related QoL and general distress levels were within the general population norms. However, more than 40% of all study participants reported melanoma‐related distress. Pancreatic cancer‐related distress was experienced by 45% of the pancreatic surveillance group. Determinants of cancer‐related distress were a first‐degree relative with melanoma or pancreatic cancer, increased cancer risk perception, and poor general health perception. Over 80% of the participants felt that the benefits of cancer surveillance outweigh the disadvantages. Conclusion In conclusion, confirmed and at‐risk carriers of the CDKN2A PV under cancer surveillance experienced similar levels of QoL and general distress compared to the general population. However, cancer‐related worry was substantial in this population. These findings can help identify individuals who may benefit from psychological support.